Design and synthesis of a bifunctional linker for N-linked glycopeptide synthesis - Lin, Desmond Junjie (Nanyang Technological University, 2022)
N-linked glycopeptides and cyclic peptide are an important class of compounds. Many of these naturally occurring compounds possess therapeutic value which could be used for treating antimicrobial resistance infections. However, these compounds were under-utilized for drug discovery as it is difficult to purify them from natural product and synthesis of these compounds in large quantity is laborious. Throughout the last few decades, there has been an increasing number of reports on total synthesis of these compounds with biological significance and novel methodology for synthesizing these valuable compounds at ease. Recognizing the significance of these compounds, thus, the aim of my thesis is to contribute to this field of research by expanding the toolbox for peptide ligation with new methodology. This thesis starts off with an overview of novel methodologies which have been utilized in peptide ligation and synthesis of glycopeptide in the past few decades. In the next chapter, it describes my work in designing and synthesis of a bifunctional linker that could facilitate the synthesis of N-glycopeptide through native chemical ligation and “traceless” Staudinger ligation. The reaction process resembles sugar assisted ligation and dual native chemical ligation with the exception that no additional auxiliary removal step is required after the ligations. Lastly, this thesis will end with third chapter exploring and discussing on macrocyclization of peptide with our designed linker via two potential pathways, namely, native chemical ligation based macrocyclization and “traceless” Staudinger ligation based macrocyclization.